BOʻLAJAK TABIIY FAN OʻQITUVCHILARINING KASBIY KOMPETENTLIKNI RIVOJLANTIRISH - Yakubova, B. (SCIENCE and SOCIETY, 2025)
To successfully complete the task of improving the quality of education, an urgent issue of higher education is the transition from an «erudite approach» to learning in the higher education system based on the «three KSS - knowledge, skill, skills» to a «competence-based approach» based on the formation of practical professional experience (the graduate becomes its master, the future of his business).